Enterprise Architecture Design of PT Hariansyah Karya Group Information System Using TOGAF ADM - Seli Puspita Sari; Reza Andrea; Husmul Beze (TEPIAN, 2024)
The rapid development of information technology provides great benefits in the business world, but its utilization must be aligned with industry goals to avoid failures arising from lack of planning PT Hariansyah Karya Group is a service provider company with various business units under its auspices facing challenges in selecting and implementing information systems and information technology in accordance with business needs. This research focuses on designing an integrated enterprise architecture using the The Open Group Architecture Framework (TOGAF) framework and the Architecture Development Method (ADM) to meet the business needs of PT Hariansyah Karya Group and analyze business needs and design appropriate architectural solutions. The research includes five main phases of TOGAF ADM: Preliminary Phase, Architecture Vision, Business Architecture, Information Systems Architecture, and Technology Architecture. The results of the research are used as a guide for developing an integrated information system at PT Hariansyah Karya Group that can increase operational efficiency, improve coordination between business units, and support company growth to adapt to technological developments. In addition, this research aims to improve the performance and efficiency of business processes at PT Hariansyah Karya Group after the implementation of the new enterprise architecture. With good enterprise architecture planning and in accordance with business strategy, PT Hariansyah Karya Group is expected to optimize its business processes and reduce the risk of information system implementation failure.